Moving towards redistributive and transformative social security? Gendered social and economic outcomes in South Africa - Sophie Plagerson; Tessa Hochfeld; Lauren Stuart (United Nations Research Institute for Social Development (UNRISD), 2017)
This paper explores whether South Africa's social security policies offer consistent, synergistic and long-term positive impacts on poverty and gender, by interrogating the redistributive and transformative outcomes of three different kinds of social security instruments. The instruments examined are the Child Support Grant as an example of social assistance, the Unemployment Insurance Fund as an example of social insurance, and the Expanded Public Works Programme's Social Sector as an example of public works. The programmes have some similarities in that they are all based on trying to address poverty in pro-poor, redistributive ways that pay attention to the inequities of the past. Designs are very different, but all evidence innovative thinking and attempts to engage with gender inequality. Overall, the CSG does much better than the other instruments in relation to redistribution and transformative gender effects. However, the effects across the social security spectrum are disappointing, with limited achievements in the UIF and EPWP especially, although gendered redistribution is taking place in all cases. Social transformation is lagging behind, and the problems can be largely laid at the door of implementation inefficiencies and unresponsive institutions.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330